Characterizing intersecting social determinants of health during pregnancy: a descriptive cross-sectional analysis from a northern New England health system - Dev, Alka; Allen, Sophia E.; Cass, Ilana; Canavan, Chelsey R.; Velmineti, Vinisha; Goodman, Daisy J. (Frontiers in Medicine, 2025)
ObjectiveWe aimed to characterize the prevalence and co-occurrence of social determinants of health among pregnant individuals during prenatal care in a single rural-based health system in the United States.Context and caseThis community case study describes the implementation and findings of universal screening for social determinants of health among all individuals initiating prenatal care at four OB-GYN clinics in a single health system between January 2022 and December 2023. Antenatal sites spanned both small urban and rural settings, with a subset of deliveries occurring at a rural, tertiary care medical center. Social determinants, including financial stress, food insecurity, housing instability, transportation issues, social isolation, and health literacy, were assessed using a screening tool embedded in the electronic health record (EHR). We used descriptive statistics and UpSet Plots to describe these determinants and their co-occurrence patterns in relation to patient characteristics.FindingsAmong 2,222 pregnant individuals who completed screening, 16.7% reported at least one social determinant, and 7.8% reported two or more. Among patients who screened positive for only one determinant, the most common concern was social isolation (38.9%), followed by financial stress (27.8%). Among those with two or more determinants, the most common items were financial stress (75.1%), food insecurity (67.6%), and housing instability (56.1%). Combinations of food insecurity, housing instability, and financial stress affected nearly one in 10 patients.ConclusionSocial isolation emerged as a significant concern for non-urban pregnant women who had no other reported social determinants. However, determinants also co-occurred, particularly housing and food insecurity with financial stress. This descriptive analysis provides foundational data for future research examining associations between intersecting social determinants and maternal–infant health outcomes. Universal screening is critically important for identifying patients with high social risk.